Effect of polymer concentration on matrimid 5218 based-carbon membrane for H2 separation - Mohd Syafiq, Sharip; Norazlianie, Sazali; Fatin Nurwahdah, Ahmad (Universiti Teknologi Malaysia, 2020)
Hydrogen (H2)-based economy development is expected to create extensive need for efficient collecting strategies of fairly high purity H2. The aim of a H2-selective membrane is to manipulate H2’s high diffusivity characteristics as well as to restrict the outcome of lower solubility. Carbon membranes offer high potential in gas separation industry due to its highly permeable and selective. Therefore, this study aims to investigate the effect of carbonization parameter, i.e., polymer concentration on the gas separation properties. Matrimid 5218 was used as a precursor for carbon tubular membrane preparation to produce high quality of carbon membrane via carbonization process. The polymer solution was coated on the surface of tubular ceramic tubes using dip-coating method. Matrimid 5218-based carbon tubular membranes were fabricated and characterized in terms of its structural morphology, chemical structure, thermal stability, and gas permeation properties by using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and pure gas permeation system, respectively. The polymer solution containing 15 wt% Matrimid 5218 shows the best formulation for the preparation of Matrimid 5218-based carbon tubular membrane. The highest H2/N2 selectivity of 401.08±2.56 was obtained for carbon membrane carbonized at 800oC with heating rate of 2oC/min.